Farmakoterapie demencí - Pidrman, Vladimír (Via practica, 2008)
The author describes basic steps in the pharmacotherapy of dementia, effects of modern drugs and approaches in the treatment of dementia. Basic principles in the treatment of dementia are summarized in the end of the article.
Keywords: Rivastigmine; Dementia; Donepezil; donepezil; Memantine; Humans; cholinesterasové inhibitory; memantin; lidé; Galantamine; Cholinesterase Inhibitors; rivastigmin; galantamin; demence